Association of serum albumin and aspartate transaminase with 5-year all-cause mortality in HIV/hepatitis C virus coinfection and HIV monoinfection. (2nd January 2017) - Scherzer, Rebecca; Heymsfield, Steven B.; Rimland, David; Powderly, William G.; Tien, Phyllis C.; Bacchetti, Peter; Shlipak, Michael G.; Grunfeld, Carl
Abstract : Objective: Liver disease markers have been associated with mortality in HIV-infected individuals in the modern era of effective antiretroviral therapy. Our objective was to determine which markers are most predictive of mortality in HIV-monoinfected and HIV/hepatitis C virus (HCV)-coinfected persons. Research design and methods: We measured serum albumin, total protein, calculated globulin, aspartate transaminase (AST), and alanine transaminase in 193 HIV/HCV-coinfected and 720 HIV-monoinfected persons in the study of Fat Redistribution and Metabolic Change in HIV Infection. We evaluated associations of each marker with 5-year, all-cause mortality, adjusting for cardiovascular, HIV-related factors, inflammation, renal disease, muscle, and adiposity. Results: After 5 years of follow-up, overall mortality was 21% in HIV/HCV-coinfected and 12% in HIV-monoinfected participants. After multivariable adjustment, lower albumin and higher AST were independently associated with increased mortality. Lower albumin was associated with 49% increased odds of mortality overall [per 0.5 g/dl decrease, 95% confidence interval (CI): 1.2–1.9]; the association was stronger in HIV/HCV-coinfected [odds ratio (OR) = 2.1, 95% CI: 1.4–3.2] vs. HIV-monoinfected (OR = 1.3, 95% CI: 1.0–1.7; HCV-by-albumin interaction: P = 0.038). Higher AST was associated with 41% increased odds of mortality (per AST doubling; 95% CI: 1.1–1.8); associations were much stronger among HIV/HCV-coinfected (OR = 2.5, 95% CI: 1.5–4.1) than HIV-monoinfected (OR = 1.1, 95% CI: 0.8–1.5; HCV-by-AST interaction: P = 0.0042). Conclusion: Lower serum albumin and higher AST appear to be important mortality risk factors in HIV/HCV-coinfection, but much less so in HIV-monoinfected individuals. The association of low albumin with mortality may reflect its role as a negative acute phase response protein. AST levels do not appear to be useful in predicting mortality in HIV-monoinfection and should be considered primarily in the context of HCV-coinfection. Abstract : Supplemental Digital Content is available in the text